VI Simpósio de Iniciação Científica Júnior - 2015 - Biazin, Damares Tomasin; Santos, Fernando Pereira dos; Trevisan, Ana Claudia Cerini; Souza, Denise Martins Américo de (Publicação Eventos Científicos, 2021)
VI Simpósio de Iniciação Científica Junior - 2015